2012
DOI: 10.1007/s00455-012-9394-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Functional Outcomes and Patient Perspective Following Altered Fractionation Radiotherapy with Concomitant Boost for Oropharyngeal Cancer

Abstract: Background: With no long-term data available in published research to date, this study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 50 publications
5
69
1
Order By: Relevance
“…As a consequence, in more recent literature there has been increased consideration of the functional outcomes and changes to quality of life (QoL) associated with dysphagia in the HNC population (Llewellyn, Weinman, McGurk, & Humphris, 2008;Lovell, Wong, Loh, Ngo, & Wilson, 2005;Nguyen et al, 2005). Whilst such research has furthered our understanding of the impact of dysphagia following HNC management, the majority of studies to date have applied quantitative methods to measure the extent of functional change (Barringer, Hutcheson, Sturgis, Kies, & Lewin, 2009;Cartmill, Cornwell, Ward, Davidson, & Porceddu, 2011a;Cartmill et al, 2012;Jensen et al, 2007) or change in QoL (Lovell et al, 2005;Maurer et al, 2011;Nguyen et al, 2005). The value of taking a quantitative approach has been to confirm that a problem exists (Llewellyn et al, 2008;Lovell et al, 2005;Murry, Madasu, Martin, & Robbins, 1998;Nguyen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, in more recent literature there has been increased consideration of the functional outcomes and changes to quality of life (QoL) associated with dysphagia in the HNC population (Llewellyn, Weinman, McGurk, & Humphris, 2008;Lovell, Wong, Loh, Ngo, & Wilson, 2005;Nguyen et al, 2005). Whilst such research has furthered our understanding of the impact of dysphagia following HNC management, the majority of studies to date have applied quantitative methods to measure the extent of functional change (Barringer, Hutcheson, Sturgis, Kies, & Lewin, 2009;Cartmill, Cornwell, Ward, Davidson, & Porceddu, 2011a;Cartmill et al, 2012;Jensen et al, 2007) or change in QoL (Lovell et al, 2005;Maurer et al, 2011;Nguyen et al, 2005). The value of taking a quantitative approach has been to confirm that a problem exists (Llewellyn et al, 2008;Lovell et al, 2005;Murry, Madasu, Martin, & Robbins, 1998;Nguyen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Both acute and long-term swallowing dysfunction may occur. Cartmill et al [14] reported that swallowing function was significantly worse 2 years post-treatment compared with baseline.…”
Section: Timingmentioning
confidence: 97%
“…In total, 11 studies or reviews discussed dysphagia assessment [3,4,8,9,14,[18][19]21 && ,23,29-30] (Tables 3 and 4). …”
Section: Assessing Dysphagiamentioning
confidence: 99%
See 1 more Smart Citation
“…Head and neck cancer (HNC) patients have challenges clustering around dysphagia, xerostomia, pain, and weight loss [3][4][5]. Dysphagia is considered the most prominent complication to HNC treatment as it impacts physical function and reduces quality of life (QoL) [6,7].…”
mentioning
confidence: 99%